Transformasi Nilai Adab Dan Akhlaq Dalam Halaqah Kreatif Tadabbur Al-Qur’an: Studi Kasus Pada Komunitas Balai Dakwah Sragen - Dhany Puspita; Abu Hanifah; Muriyanto Muriyanto (Journal of Innovative and Creativity, 2025)
This research aims to explore the process and impact of creative Qur’anic tadabbur study circles (halaqah) in shaping participants’ manners (adab) and moral character (akhlaq) at Balai Dakwah Sragen. The study is motivated by the need for an Islamic character education model that transcends cognitive delivery and engages the affective and practical aspects of daily life. Employing a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation. Findings indicate that the creative halaqah serves as an effective medium for the contextual internalization of Qur’anic values. Through interactive methods such as tadabbur journaling, reflective discussions, and visual interpretation of verses, participants exhibited notable positive behavioral changes, particularly in emotional control, interpersonal conduct, and spiritual awareness. A key supporting factor was the integration of personal experiences with a supportive learning community. However, challenges remain in maintaining the consistency of moral transformation outside the halaqah environment. This study contributes to the development of a transformative, community-based Islamic education model. It recommends the integration of creative halaqah methods into character-building programs in Islamic institutions and da’wah organizations.